Spectrum of Synovial Sarcoma-clinicopathological and Immunohistochemical Correlation - GV, Sunandalakshmi; Chougani, Sujitha; Kharidehal, Durga; V, Ravi Sankar; Vissa, Santhi (Annals of Pathology and Laboratory Medicine, 2020)
Background: Synovial sarcoma is the common adult soft tissue sarcomas affects the lower extremities. In poor resource settings, characterization by molecular methods may not be feasible always. This study is aimed to evaluate Sensitivity and Specificity of Transducin-like enhancer of split 1 (TLE1) immunohistochemical expression in Synovial sarcomas (SS) and its histological mimics and to study the clinicopathological features of Synovial sarcoma. Method: A prospective study of two years duration from September 2013 to September 2015 conducted at the Department of Pathology, MNJ Institute of Oncology and Regional Cancer Centre, Redhills, Hyderabad. Total number of Synovial sarcomas was 30. All original H & E section of the tumor are reviewed and Immunohistochemistry (IHC) analysis was carried out on TLE1 mouse monoclonal antibody (TMA) blocks using TLE1 Antibody. Results: The Median age was 30 years. The most common site of involvement was lower limbs. The most common mode of presentation was painless swelling. The most common variant of Synovial sarcoma was monophasic Spindle in 19 cases. Total number of TLE1 positive cases of Synovial sarcoma was 93.3%. Total number of SS mimics showing TLE1 positivity was30%. TLE1 showed Sensitivity 93.3% and Specificity- 73.3%. In the present study negative predictive value is 91.6% and the positive predictive value is 77.7%. Conclusion: All small round blue cell tumors should be kept in mind while diagnosing poorly differentiated SS. TLE1 is a very sensitive marker for synovial sarcoma.TLE 1 is a highly sensitive marker for synovial sarcoma, but is less specific because of its positive expression in other mesenchymal tumors.